JAMUR ENTOMOPATOGEN ASAL TANAH LEBAK DI SUMATERA SELATAN DAN POTENSINYA SEBAGAI AGENSIA HAYATI WALANG SANGIT (LEPTOCORISA ORATORIUS (F.)) - Effendy TA, Robby Septiadi, Abdullah Salim & Abdul Mazid . (Universitas Lampung, 2010)
Entomopathogenic fungi from the lowland soil of South Sumatera and their potential as biocontrol agents of Stink Bug (Leptocorisa oratorius (F.)). The purpose of this research was to explore and examine the potential of soil borne entomopathogenic fungi from South Sumatera as biological agents of Leptocorisa oratorius (F). Soil used for trapping entomopatogenic fungi, was taken from five locations in South Sumatera. Percentage of nymph mortality was analyzed by using analysis of variance and arranged in Completely Randomized Design. LT50 of nymph mortality was determined with Probit Analysis. Entomopathogenic fungi found in this research were Beauveria bassiana and Metarhizium sp. Stink bug mortality due to B. bassiana isolates reached 40-73.3% and Metarhizium sp. reached 56.7-70%. The results showed that Metarhizium isolates were more virulent than B. bassiana isolates. The viability of B. bassiana conidia did not decrease during sub-culturing. Sub-culturing did not influence the mortality of stink bug nymph but it prolonged the LT50 of the stink bug.